FOOD CULTURE ACCULTURATION OF MARTABAK CUISINE ORIGINALLY FROM INDIA TO INDONESIA - Rianti, Angelina (Studi Budaya Nusantara, 2018)
Abstract Martabak is a popular street food snack that is easy and widely found in the countries of India, Indonesia, Saudi Arabia, and Malaysia. Martabak was first introduced in India, precisely in the region of Kerala. Martabak is an appetizer, side dish or some kind of snack. Indian traders and people who migrate to other countries bring and introduce martabak and become as a process of acculturation of food culture. Martabak itself introduced from India as a dish of stuffed fried bread with topping like meat and vegetables with main ingredient of eggs. In Indonesia, the culture of martabak food is adjusted and modified to form a new sweet martabak textured like pancake that has a thicker texture than savoury martabak. In Saudi Arabia, martabak is also known as two types which are sweet and savoury and often referred as